Alasdair MacIntyre’s Fallibilistic Interpretation of Aquinas’ Theory of Truth (Nóema, 2017)
This paper seeks to shed some light on the possibility of a fallibilistic interpretation of Aquinas’ theory of truth, as attributed to him by Alasdair MacIntyre. Prima facia, it seems strange to read into Aquinas’ theory of truth a kind of fallibilism which approaches Poppers’ thought, especially taking into account the theological and optimistic view of Aquinas concerning the capacity of the intellect to arrive at truth. In this paper, I will argue from two perspectives, that is, the mechanisms of the intellect and Aquinas’ account of first principles for the possibility of a qualified version of fallibilism, which retains its differences from the Popperian version.
Keywords: Aquinas; MacIntyre; Fallibilism; Intellect; Discursive Reasoning